High-permeability zones in folded and faulted silicified carbonate rocks – Implications for karstified carbonate reservoirs. (June 2021) - La Bruna, Vincenzo; Bezerra, Francisco H.R.; Souza, Victor H.P.; Maia, Rubson P.; Auler, Augusto S.; Araujo, Renata E.B.; Cazarin, Caroline L.; Rodrigues, Marcos A.F.; Vieira, Lucieth C.; Sousa, Maria O.L.
Abstract: Ascending hydrothermal fluid flow and subsequent hypogene karstification can control the formation of high-permeability zones in folded or faulted carbonate rocks. This study presents a multidisciplinary and multiscale approach to investigate the relationships between regional deformation and subseismic karst conduits along fracture corridors. We investigate the Cristal Cave Karst System, which is 6.7 km long and occurs in Mesoproterozoic carbonate-siliciclastic units affected by hydrothermal silicification in the São Francisco Craton, Brazil. Based on integrated techniques of ALOS PALSAR imagery, structural field surveys, stratigraphic and laboratory analyses in the caves and the surrounding surface outcrops, we highlight the following points: (1) the cave system occurs in a regional folded sector; (2) the internal architecture of the large regional folds is composed of subseismic folds; (3) fracture corridors occur along the subseismic fold hinges, forming high-permeability zones; and (4) the principal cave passages, which are oriented NNE-SSW, are concentrated along these fold hinges. We discuss the results in terms of a spatiotemporal conceptual model and unravel the deformation and karstification stages, which are characterized by the development of (i) precontractional and (ii) contractional structural networks followed by (iii) hydrothermal silicification and karstification processes. This cave system can be used as an analog for deformed, silicified, and karstified carbonate reservoirs, allowing for the in situ characterization of subseismic structural features. This study provides the key for first-order prediction and characterization of high-permeability zone internal structures, where both deformation and karstification processes occur. Graphical abstract: Image 1 Highlights: The internal architecture of high-permeability zones is composed of karst conduits. Fracture corridors form high-permeability zones along fold hinges. Subseismic structures control hypogene karst processes. Subseismic karst conduits are related to regional deformation and are predictable.